A case study on vocabulary learning strategies in Malaysia: implications for teaching and learning - Supian, Nadya; Mohd. Asraf, Ratnawati (SITE Australia Ltd., 2019)
Within the context of learning English for specific purposes (ESP), vocabulary acquisition plays a crucial role in the development of written and spoken communication in both technical and non-technical industries. Thus, the use of vocabulary learning strategies would determine both learners' fluency as well as confidence in communicating. This paper analyzes the factor structure of the most frequently used vocabulary learning strategies by Malaysian ESL learners studying at a higher learning institution. The implications of the findings are discussed, and suggested practices for implementing vocabulary learning strategies in the language classroom, such as mobile-assisted language learning and game-based language learning; are presented.